2020
DOI: 10.31584/jhsmr.2020746
|View full text |Cite
|
Sign up to set email alerts
|

Necessity of In-hospital Neurological Observation for Mild Traumatic Brain Injury Patients with Negative Computed Tomography Brain Scans

Abstract: Objective: The authors aimed to evaluate the necessity of in-hospital neurological observation for mild traumatic brain injury (TBI) patients, who did not have any evidence of intracranial injury from initial computed tomography (CT) brain scans. Material and Methods: We retrospectively reviewed mild TBI patients with initial negative CT brain scans, receiving treatment at Songklanagarind hospital between January and December, 2018. All patients were observed in the emergency department short stay observation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…8 Nomograms built from a model of logistic or Cox regression have been used in neurosurgery as diagnostic or prediction tools. [9][10][11] Tunthanatip et al developed a nomogram for predicting positive findings following CT of the brain in pediatric patients with TBI and reported an area under the receiver operating characteristic (ROC) curve (AUC) of 0.71. 11 After conducting a literature review, we found a lack of evidence comparing predictive performance between ML and the nomogram with the same clinical outcome.…”
mentioning
confidence: 99%
“…8 Nomograms built from a model of logistic or Cox regression have been used in neurosurgery as diagnostic or prediction tools. [9][10][11] Tunthanatip et al developed a nomogram for predicting positive findings following CT of the brain in pediatric patients with TBI and reported an area under the receiver operating characteristic (ROC) curve (AUC) of 0.71. 11 After conducting a literature review, we found a lack of evidence comparing predictive performance between ML and the nomogram with the same clinical outcome.…”
mentioning
confidence: 99%
“…However, a low prevalence of moderate or severe pediatric TBI was observed in previous studies as 7.5%–29.8% for moderate TBI and 7.9%–13% for severe TBI, respectively. [ 3 4 5 25 ] A multicenter study or meta-analysis studies were previously conducted in an attempt to resolve this limitation, while the propensity score approach was also adopted to adjust the selection bias and non-randomized study design. [ 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, selecting GBM patients by predicted favorable prognosis has been proposed for the likelihood of TMZ cost-effectiveness in real-world situations. 24 Nomogram is one of the clinical prediction tools (CPT) that have been used for various diseases such as cancer, 25 trauma, 26,27 or degenerative disease. 28 Therefore, we proposed a web-based nomogram for prognostication that will be applied for selecting patients with a favorable prognosis when low-or middle-income settings need to allocate resources.…”
Section: Discussionmentioning
confidence: 99%